(untitled) (Emancipação, 2024)
This article shares the results of a research that analyzed ethical transversality in the curricular structure of undergraduate Social Work courses in public universities in the state of Paraná, Brazil. It is a qualitative, descriptive, and exploratory research that includes bibliographic and document analysis. The study investigated four Social Work courses from three universities in Paraná: State University of Londrina, Western Paraná University, and State University of Ponta Grossa. The results indicated that the 1986 Curricular Guidelines were constructed from a perspective of totality, primarily translated into the proposal of an articulated education with three core foundations, which should guide the syllabuses of disciplines and other activities concerning professional education. It was observed that although ethics is present in the syllabuses of different disciplines in the analyzed courses, its transversality is not yet explicitly stated in the curricular structures, pointing to some challenges regarding ethics-focused education. This requires strengthning the articulation between disciplines based on the intrinsic relationship between them and the theoretical-methodological, ethical-political, and technical-operational dimensions, which constitute the profession.